Antenatal depression and its predictors among HIV positive women in Sub-Saharan Africa; a systematic review and meta-analysis - Abebe, Gossa Fetene; Alie, Melsew Setegn; Adugna, Amanuel; Asemelash, Daniel; Tesfaye, Tamirat; Girma, Desalegn; Asres, Abyot (Frontiers in Psychiatry, 2024)
Background Antenatal depression in Human Immunodeficiency Virus (HIV) positive pregnant women can have significant adverse effects on both the mother and newborns, yet it is often overlooked in pregnancy care in Sub-Saharan Africa (SSA). Despite this, there is limited data on the combined prevalence of antenatal depression and its predictors among HIV-positive women in the region. Objective To assess the pooled prevalence of antenatal depression and its associated factors among HIV-positive women in SSA. Methods All primary cross-sectional studies published before 1st January/2024, were included. We conducted searches in relevant databases; PubMed, HINARI, Web of Science, PsycINFO, Psychiatry Online, ScienceDirect, and Google Scholar. The Joanna Briggs Institute checklist was used to critically appraise the selected studies. To assess heterogeneity among the studies, we utilized the I2 test. Publication bias was evaluated using a funnel plot and Egger’s test. The forest plot was used to present the combined proportion of antenatal depression and odds ratio, along with a 95% confidence interval. Results The pooled prevalence of antenatal depression among HIV-positive women in Sub-Saharan Africa was found to be 30.6% (95% CI, 19.8%-41.3%). Factors significantly associated with antenatal depression among HIV-positive women in SSA included being unmarried (AOR: 3.09, 95% CI: 1.57 – 6.07), having a previous history of depression (AOR: 2.97, 95% CI: 1.79 – 4.91), experiencing intimate partner violence (IPV) (AOR: 2.11, 95% CI: 1.44 – 3.09), and experiencing stigma (AOR: 1.36, 95% CI: 1.05 – 1.76). Conclusion High prevalence of antenatal depression among HIV-positive women in SSA underscores the need for prioritizing identification and management. Interventions addressing factors like IPV and stigma, along with training for healthcare providers in recognizing symptoms and providing support, are recommended. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024508236.